Effects of Thelytokous Parthenogenesis-Inducing Wolbachia on the Fitness of Trichogramma dendrolimi Matsumura (Hymenoptera: Trichogrammatidae) in Superparasitised and Single-Parasitised Hosts - Zhou, Jin-Cheng; Zhao, Qian; Liu, Shi-Meng; Shang, Dan; Zhao, Xu; Huo, Liang-Xiao; Dong, Hui; Zhang, Li-Sheng (Frontiers in Ecology and Evolution, 2021)
Thelytokous Wolbachia-infected Trichogramma species have long been considered as biological control agents against lepidopteran pests in agriculture and forestry. Wolbachia has been suggested to increase the probability of the superparasitism of Trichogramma, but the fate of infected offspring in the superparasitised host is still unknown. The present study aimed to evaluate the fitness of thelytokous Wolbachia-infected (TDW) and bisexual Wolbachia-free (TD) Trichogramma dendrolimi Matsumura (Hymenoptera: Trichogrammatidae) lines in superparasitised or single-parasitised hosts. The results showed that irrespective of whether Trichogramma wasps were developed from superparasitised or single-parasitised hosts, the TDW line was characterized by reduced fitness, including lower fecundity, shorter longevity, and smaller body size of F1 offspring, and lower emergence rate of F2 offspring than the TD line. This was not true for the survival rate and developmental time of F1 offspring. Additionally, the fitness parameters of T. dendrolimi that developed from superparasitised hosts were lower compared with that of T. dendrolimi that developed from single-parasitised hosts. Interestingly, Wolbachia-infected females had higher dispersal capacity than bisexual females when they developed from superparasitised hosts. The results indicated that Wolbachia negatively affects fitness of T. dendrolimi, but enhance dispersal capacity of T. dendrolimi females in superparasitism condition. Further studies need to be carried out to select the best line that will allow Wolbachia and their host Trichogramma to be better adapted to one another.